Implementation of multilingual support of the European Multicenter Study about Spinal Cord Injury (EMSCI) ISNCSCI calculator - Schuld, Christian; Franz, Steffen; Schweidler, Joachim; Kriz, Jiri; Hakova, Renata; Weidner, Norbert; Rupp, Rüdiger; Liu, Nan (Spinal cord, 2022)
OBJECTIVES: Since their introduction, electronic International Standards for Neurological Classiﬁcation of Spinal Cord Injury (ISNCSCI) calculators have evolved to powerful tools providing error-free ISNCSCI classiﬁcations in education, research and clinical practice. For increased accessibility and dissemination, a multilingual support is mandatory. The aim of this work was to setup a general multilingual framework for the freely available ISNCSCI calculator (https://ais.emsci.org) of the European Multicenter Study about Spinal Cord Injury (EMSCI). - METHODS: The graphical user interface (GUI) and PDF export of the ISNCSCI worksheet were adapted for multilingual implementations. Their language-dependent content was identiﬁed. These two steps called internationalization have to be performed by a programmer in preparation of the translations of the English terms into the target language. This step following the internationalization is called localization and needs input by a bi-lingual clinical expert. Two EMSCI partners provided Standard Mandarin Chinese and Czech translations. Finally, the translations are made available in the application. - RESULTS: The GUI and PDF export of the ISNCSCI worksheet were internationalized. The default language of the calculator is set according to the user’s preferences with the additional possibility for manual language selection. The Chinese as well as a Czech translation were provided freely to the SCI community. - CONCLUSIONS: The possibility of multilingual implementations independent from software developers opens the use of ISNCSCI computer algorithms as an efﬁcient training tool on a larger scale. Spinal Cord (2022) 60:37-44; https://doi.org/10.1038/s41393-021-00672-y